2022
DOI: 10.1136/bmjopen-2021-057246
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functioning status of COVID-19 survivors: a prospective observational evaluation of a cohort of patients surviving hospitalisation

Abstract: ObjectivesThe study investigated the long-term functional status of hospitalised COVID-19 survivors to explore and document their functional situation.DesignThis prospective observational study assessed 801 COVID-19 survivors at 3–11 months after hospital discharge. It analyses participants' sociodemographic background, COVID-19 clinical manifestations, and clinical and functional evaluations.SettingTertiary-level university hospital in São Paulo, Brazil.ParticipantsStudy participants are COVID-19 survivors ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…A cohort study of 318 older patients who survived hospitalization for COVID-19 showed a 36% prevalence of functional limitations 3 months after discharge. 13) Consistent with our findings, Battistela et al 14) found that 71% of COVID-19 survivors reported limitations in their daily activities 11 months post-discharge from the hospital. In addition, a Chinese ambispective cohort study including data from Values are presented as median (interquartile range) or number (%).…”
Section: Discussionsupporting
confidence: 91%
“…A cohort study of 318 older patients who survived hospitalization for COVID-19 showed a 36% prevalence of functional limitations 3 months after discharge. 13) Consistent with our findings, Battistela et al 14) found that 71% of COVID-19 survivors reported limitations in their daily activities 11 months post-discharge from the hospital. In addition, a Chinese ambispective cohort study including data from Values are presented as median (interquartile range) or number (%).…”
Section: Discussionsupporting
confidence: 91%
“…Almost all the studies used valid study tools and criteria for the assessing persistent symptoms. For assessing one of the most common and persistent symptoms, dyspnea, tools such as Dyspnoea-12 (ID 9, 19) [ 22 , 32 ], Self-Evaluation of Breathing Questionnaire (SEBQ) (ID 12) [ 25 ], The King’s Brief Interstitial Lung Disease questionnaire (ID 33) [ 46 ], etc. were used.…”
Section: Resultsmentioning
confidence: 99%
“…A large cohort study on over 800 people in Brazil who had been hospitalised for at least one day due to COVID-19 found that 6 months after discharge, 71% of survivors (n = 567) were experiencing limitations in their daily activities, Healthcare 2023, 11, 3085 2 of 10 and 6% (n = 45) rated this as severe. Pain and discomfort (65%), breathlessness (65%), and anxiety and depression (57%) were also reported among this cohort [7]. Abnormal mucus production, systemic inflammation, lung fibrosis, and post-viral inflammation have also been observed [4,8,9].…”
Section: Introductionmentioning
confidence: 63%